Restaurant Tax Calculation Application and Service Fees for Tax Reporting: (Study At One of The Restaurants in Cimahi) - Rohmatika, Irma; Andhita, Miranti; Irawan, Debi; M, Farhanah Fitria; Abdurahman, Fikri Irawan (LPPM STMIK Mardira Indonesia, 2024)
The Restaurant levy is a government or city-managed levy that can augment the local revenue of Cimahi City. Certain restaurants frequently impose an additional service fee. One of the restaurants in Cimahi still uses a semi-computerized or semi-EDP (Electrical Data Processing) system, which results in inefficient calculation of the Restaurant Tax and Service Fee and slow reporting to the Local Government. Descriptive research is a method that focuses on providing a detailed and systematic analysis of specific phenomena or qualities. The system development methodology employed is object-oriented analysis and design (OOAD). The Nikmat Sunda Restaurant program, accessed through the web, can carry out automated calculations and act as a data resource to enhance time efficiency. Hence, the Restaurant Tax and Service Fee calculation can serve as a foundation for generating Restaurant Tax reports.